(untitled) (Palimpsesto, 2021)
This paper explores the conformation of the Chilean magazine field that existed between the 1960s and the 1973 coup, understanding the period as a time deeply signed by the relationship between politics and culture. In this way, we seek to map and analyze the conformation and proliferation of the Chilean magazine field, crossed by a maturity of the country’s cultural and university institutional systems, as well as by the proliferation of various independent spaces and groups that acted as magazine producers, a task that prompts us to discuss a taxonomy appropriate to the Chilean case with its particularities.